Seasonal predictability of the Indian Summer Monsoon : What role do land surface conditions play? - BECKER, B. D.; SLINGO, J. M.; FERRANTI, L.; MOLTENI, F. (MAUSAM, 2001)
Anomalous springtime snow amounts over Eurasia may provide long term memory to the climate system by affecting the land surface energy and moisture budgets. In turn the anomalous land surface conditions introduced by snow anomalies may influence monsoon variability. In this paper, results from a programme of seasonal forecast ensembles are used to address, specifically, the influence of western Eurasian land surface conditions on the variability and hence predictability of the Indian summer monsoon. The factors that are important for establishing spring time land surface conditions over western Eurasia, particularly snow amounts are also investigated. The results have shown that high snow amounts over western Eurasia are linked to La Nina, suggesting that the El-Nino/Southern Oscillation (ENSO) has an influence on the wintertime climate of Eurasia. The signature of these snow depth anomalies is carried through to the summer in terms of changes in soil wetness and surface temperature. An ensemble of summer integrations with climatological sea surface temperature (SST) has been used to investigate the impact of these anomalous land surface conditions on monsoon variability. The results have shown that the monsoon circulation is substantially weakened in association with above normal snow amounts over western Eurasia, whilst All India Rainfall is slightly increased. Results from a parallel ensemble with observed SSTs show an opposite response in All India Rainfall, suggesting that the forcing by SST anomalies is potentially dominating the monsoon’s inter-annual variability. The results have demonstrated that land surface conditions can have a significant impact on the large scale monsoon circulation and to a lesser extent on Indian Summer Monsoon rainfall, although the mechanisms involved have yet to be identified. It is suggested that interactions between the mid-latitude circulation and the monsoon may hold the key to understanding the link between Eurasian land surface conditions and monsoon variability. If that is the case then predictability of this relationship is likely to be limited, due to the high level of internal variability of the mid-latitude circulation.